2016
DOI: 10.3329/bjms.v15i4.23958
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio of Second to Fourth Digit Length (2D:4D) and Heart Disease

Abstract: Objectives: The risk of getting heart diseases is unpredictable due to many predisposing factors range from lifestyle to genetic inheritance. Scientist made the discovery after studying men of various age who had suffered heart disease made a finding; the length of ring fingers (4D) are shorter than index fingers (2D) are at greater risk of premature heart attack at their early 30. Based on these facts, we carried out this project work by analyzing 2D and 4D ratios with the perspective of risk of heart disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…While the left hand digit ratio was 33.8% in the high category and 66.3% in the low category. Research conducted by Kumar et all on the students in Malaysia as subjects found high digit ratio prevalence of 55% (16). While previous studies conducted in Indonesia on YARSI University students in Central Jakarta also found a high digit ratio prevalence of 45.82% (14).…”
Section: The Correlation Between Digit Ratio With Metabolic Syndromementioning
confidence: 80%
See 1 more Smart Citation
“…While the left hand digit ratio was 33.8% in the high category and 66.3% in the low category. Research conducted by Kumar et all on the students in Malaysia as subjects found high digit ratio prevalence of 55% (16). While previous studies conducted in Indonesia on YARSI University students in Central Jakarta also found a high digit ratio prevalence of 45.82% (14).…”
Section: The Correlation Between Digit Ratio With Metabolic Syndromementioning
confidence: 80%
“…Study about digit ratio began in 2 years old children, and possibly increased the formation of digit ratio since early of life. This study leads to the hypothesis that the number of digit ratio reflects embryo's exposure to testosterone and estrogen hormones which are formed since the end of the first trimester of fetal development and remains relatively stable throughout the life, which tend to develop certain diseases in the future (14,16,17). This hypothesis has not been tested using experimental study (17).…”
Section: Introductionmentioning
confidence: 99%